Measuring the new world : enlightenment science and South America - Safier, Neil (University of Chicago Press, 2008)
Prior to 1735, South America was largely terra incognita to many Europeans. But that year, the Paris Academy of Sciences sent a joint French and Spanish mission to the Spanish American province of Quito (in present-day Ecuador) to study the curvature of the Earth at the Equator--an expedition that would put South America on the map and in the minds of Europeans for centuries to come. Equipped with quadrants and telescopes, the mission's participants referred to the transfer of scientific knowledge from Europe to the Andes as a "sacred fire" passing mysteriously through European astronomical ins